Association of human antibodies to arabinomannan with enhanced mycobacterial opsonophagocytosis and intracellular growth reduction - McShane, H; Tanner, R; Fletcher, H; Chen, T; Blanc, C; Eder, A; Prados-Rosales, R; Souza, A; Kim, R; Glatman-Freedman, A; Joe, M; Bai, Y; et al. (Oxford University Press, 2016)
Background: The relevance of antibodies (Abs) in the defense against Mycobacterium tuberculosis infection remains uncertain. We investigated the role of Abs to the mycobacterial capsular polysaccharide arabinomannan (AM) and its oligosaccharide fragments in humans. Methods: Sera from 29 healthy adults before and after primary or secondary BCG vaccination were assessed for Ab responses to AM via ELISA, and AM oligosaccharide epitopes via novel glycan microarrays. Effects of pre- and postvaccination sera on BCG phagocytosis and intracellular survival were assessed in human macrophages. Results: IgG responses to AM increased significantly at 4-8 weeks post vaccination (p<0.01) and sera were able to opsonize BCG as well as M. tuberculosis grown in both the absence and the presence of detergent. Phagocytosis and intracellular growth inhibition were significantly enhanced when BCG was opsonized with postvaccination sera (p<0.01) and these enhancements correlated significantly with IgG titers to AM (p<0.05), particularly with reactivity to three AM oligosaccharide epitopes (p<0.05). Furthermore, increased phagolysosomal fusion was observed with postvaccination sera. Conclusion: Our results provide further evidence for a role of Abmediated immunity to TB, and suggest that IgG to AM, especially to some of its oligosaccharide epitopes, could contribute to the defense against mycobacterial infection in humans.